INTESTINAL HELMINTH INFECTION AND NUTRITIONAL STATUS OF SCHOOL CHILDREN IN ENUGU STATE, NIGERIA - P. C. Okechukwu; M. O. Iwueze; C. U. Uzochukwu; A. E. Onyido (The Bioscientist)
The public health importance of intestinal helminths in endemic communities cannot be overemphasised. This study was done to investigate the effect of intestinal helminths infection on nutritional status of school children in Enugu State, Nigeria. Stool samples were collected from 2411 pupils of randomly selected primary schools and examined using direct smear and Kato Katz techniques to determine prevalence. Malnutrition among intestinal helminths infected pupils were assessed using standard anthropometric measurements. Data obtained was analysed using SPSS version 23. Of the 2411 pupils examined, 333(13.8%) were positive for various intestinal helminths parasites. Anthropometric measurements of height for age and gender revealed that 37.2% of infected pupils had heights below the normal heights. More infected males (44.9%) were below the normal heights, than the females (27.7%) (P = 0.000). Pupils aged 14years and above were the most under height than other age groups (P = 0.000). In the weight-for-age result, 51.9% infected pupils were underweight. More infected females (56.8%) than males (48.1%) were underweight (P = 0.000). All infected pupils aged 14 years were underweight (100%). Result also showed that 45.0% were malnourished, while 14.1% and 40.8% were severely malnourished and well-nourished respectively (P = 0.172). Infected male (47.9%) pupils were more (42.6%) malnourished than their female counterparts (P = 1.29). Result on body mass showed that 70.3% were severely stunted, while 18.3% had normal body mass index (BMI) (P = 0.466). The burden of Intestinal helminths infection is of public health importance mainly among children, negatively affecting their growth and development. Improved mass drug administration, proper sewage disposal, health education, improved environmental and personal hygiene are recommended for control and possible elimination.